2019
DOI: 10.1136/bmjophth-2019-000342
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of differential methylation in rare ophthalmic diseases

Abstract: Rare ophthalmic diseases have a devastating impact on a patient’s vision and consequently negatively affect their independence, ability to work and overall quality of life. Methylation is an important emerging biomarker of disease and may improve understanding of rare ophthalmic disorders. This systematic review sought to identify and evaluate literature on methylation and rare ophthalmic disease. MEDLINE, EMBASE, PubMed, Cochrane Database of Systematic Reviews and grey literature resources were searched for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Epigenetic signatures may display tissue specificity linked to disease mechanisms, however, obtaining kidney biopsy material is invasive and is not performed as part of routine clinical practice in people with DKD and T1D in the United Kingdom. Peripheral blood-based methylation biomarkers have shown promise in several clinical fields ( Moore et al, 2014 ; Agha et al, 2019 ; Cardenas et al, 2019 ; DiTroia et al, 2019 ; Henderson-Smith et al, 2019 ; Kerr et al, 2019a , b , 2020 ; Ladd-Acosta and Fallin, 2019 ; Zhou et al, 2019 ) including kidney disease ( Smyth et al, 2014b , 2018 ; Swan et al, 2015 ; Aranyi and Susztak, 2019 ; Gluck et al, 2019 ; Kato and Natarajan, 2019 ; Kerr et al, 2019b ; Park et al, 2019 ). We have previously demonstrated that blood-derived differential methylation is also reflected in kidney-derived differential methylation for CKD ( Smyth et al, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic signatures may display tissue specificity linked to disease mechanisms, however, obtaining kidney biopsy material is invasive and is not performed as part of routine clinical practice in people with DKD and T1D in the United Kingdom. Peripheral blood-based methylation biomarkers have shown promise in several clinical fields ( Moore et al, 2014 ; Agha et al, 2019 ; Cardenas et al, 2019 ; DiTroia et al, 2019 ; Henderson-Smith et al, 2019 ; Kerr et al, 2019a , b , 2020 ; Ladd-Acosta and Fallin, 2019 ; Zhou et al, 2019 ) including kidney disease ( Smyth et al, 2014b , 2018 ; Swan et al, 2015 ; Aranyi and Susztak, 2019 ; Gluck et al, 2019 ; Kato and Natarajan, 2019 ; Kerr et al, 2019b ; Park et al, 2019 ). We have previously demonstrated that blood-derived differential methylation is also reflected in kidney-derived differential methylation for CKD ( Smyth et al, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
“…54 A multiomic approach to studying disease will yield more information on inherited eye disorders than has previously been established, but as yet transcriptomics, metabolomics, proteomics and epigenomics still remain as research-based tests. 55…”
Section: Other Inheritance Patterns and Complexitiesmentioning
confidence: 99%
“…Array-based ‘epi-signature’ testing is already clinically available for some 40 inherited conditions affecting around 60 genes (45, 46). Methylation-based studies have also suggested the causative or correlative role of aberrant methylation in diverse rare inherited conditions including Kabuki Syndrome (47), Werner Syndrome(48) rare ophthalmic disease (49), orofacial cleft (50) and fucosidosis (51), either in the presence or absence of known DNA mutations. Whether deviation from a normal methylation pattern reflects alterations of genetic or epigenetic origin, expanded methylation profiling could offer the ability to detect diagnostic signals unique to the epigenome or undetectable in DNA and RNA due to lack of measurable manifestation in those materials, or due to shortcomings in current technologies or analytical approaches.…”
Section: Introductionmentioning
confidence: 99%